2014
DOI: 10.1080/09168451.2014.891928
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid polymorphism in the Drosophila melanogaster Dα1 (ALS) subunit enhances neonicotinoid efficacy at Dα1-chicken β2 hybrid nicotinic acetylcholine receptor expressed in Xenopus laevis oocytes

Abstract: A single amino acid polymorphism in the Drosophila melanogaster Dα1 (ALS) subunit enhances neonicotinoid efficacy at Dα1-chicken β2 hybrid nicotinic acetylcholine receptor expressed in Xenopuslaevis oocytes, Bioscience, Biotechnology, and Biochemistry, 78:4, 543-549,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Some, such as the Ser221 depicted in the framed panel on the left, directly interfere with the action of competitive agonists, like the neonicotinoids, at the ligand-binding site (Image taken from Shimada et al, 2020 ). In contrast, others are more distal and likely indirectly impact nAchR functions by modulatory activities ( a Homem et al, 2020 ; b Ihara et al, 2014 ; c Perry et al, 2008 ; d Somers et al, 2015 ; e Hikida et al, 2018 ; f Shimada et al, 2020 ; g Zimmer et al, 2016 ).…”
Section: Pharmacological Properties Of the Drosophila Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some, such as the Ser221 depicted in the framed panel on the left, directly interfere with the action of competitive agonists, like the neonicotinoids, at the ligand-binding site (Image taken from Shimada et al, 2020 ). In contrast, others are more distal and likely indirectly impact nAchR functions by modulatory activities ( a Homem et al, 2020 ; b Ihara et al, 2014 ; c Perry et al, 2008 ; d Somers et al, 2015 ; e Hikida et al, 2018 ; f Shimada et al, 2020 ; g Zimmer et al, 2016 ).…”
Section: Pharmacological Properties Of the Drosophila Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
“…Additionally, nitenpyram resistance is linked to the cooperative activity of the subunits Dα1 and Dβ2 ( Perry et al, 2008 ). Given that there are more examples of subunit-specific interactions with insecticides ( Ihara et al, 2014 ; Zimmer et al, 2016 ; Homem et al, 2020 ), the general idea is that insecticide efficacy is contingent upon specific residues and motifs in distinct subunits, supporting the endeavor of developing species-specific pesticides that discriminate between the subunits of different pentamers. Another extension of these studies is the hope that computational modeling can estimate the importance of residues and structural motifs of the nAchR subunits, and provide informed predictions concerning the evolution of insecticide resistance in the field.…”
Section: Pharmacological Properties Of the Drosophila Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these questions, we computationally modelled a full length fruit fly ( Drosophila melanogaster ) Dα1‐chicken ( Gallus gallus ) β2 nACh receptor in complex with imidacloprid, since this insect‐vertebrate hybrid nACh receptor exhibits a higher neonicotinoid sensitivity than the chicken α4β2 nACh receptor (Ihara et al, , ). The model showed that not only Arg 57 in loop G, but also Lys 140 in loop E at the Dα1‐Dα1 subunit interface interact with the nitro group of imidacloprid and Glu 78 supports this interaction by forming salt bridges.…”
Section: Introductionmentioning
confidence: 99%